An Overview of the Life Skills of Sago Processing into Bagea for the Easy Generation in Ihamahu Village, Saparua Sub-district, Central Maluku Regency - Junita L. Kundre (Peneliti.net, 2023)
This study aims to find out about the Life Skills of Processing Sago into Bagea for the Young Generation in Ihamahu Village, Saparua District, Central Maluku Regency. This research was conducted in Ihamahu Village, Saparua District, Central Maluku Regency. The approach used in this research is a descriptive approach. are the entire young generation who carry out Life Skills for Processing Sago into Bagea in Ihamahu Village, Saparua District, Central Maluku Regency. which totaled 20 people. Sampling in this study was based on the opinion of Furchan (1982.198) that sampling for descriptive research is at least 10% to 20% of the population if the population is above 100. On this basis, the total sample is taken as a sample (100%). Data is collected through Observation, Questionnaire, Interview. The technique that will be used to process and analyze research data is percentage analysis, which is a technique used to analyze data or information obtained through a questionnaire. Research concludes thatFirst.Sago Processing Life Skills Become Bagea for the Young Generation in Ihamahu Village, Saparua District, Central Maluku Regency has a significant increase, this is due to the desire for the business of making sago into bagea this comes from within yourself and other people to do it, so that you can increase the business of making sago bagea as a daily necessity for the welfare of your family in the future.Second.Life Skills for Processing Sago into Bagea in Ihamahu Village, Saparua District, Central Maluku Regency, from the aspect of knowledge about making sago bagea is very good because this business is obtained through the transformation of knowledge and skill values ​​that have been passed down from generation to generation and have been occupied for more than 3 years, so with that can help families for children's educational needs and daily needs.Third.Processing Sago into Bagea for the younger generation in Ihamahu Village, Saparua District, Central Maluku Regency, in terms of attitudes and knowledge aspects, has shown a positive attitude in stimulating motivation in managing sago bagea as part of natural resources that have been processed to be used as livelihoods in efforts improve family welfare.